Use of a neuroprotective extract and pharmaceutical preparation thereof. - Mohamed, Suhaila; Md Jaffry, Juliana; Ahmad, Intan-Natasya (2009)

(untitled)
The present invention disclosed an extract having neuroprotective property prepared from a plant of the family Palmae, which is capable in preserving neurons against damage caused by oxidation, ageing and/ or nitric oxide deficiency. Also disclosed is a pharmaceutical preparation and a comestible preparation comprising the extract as an active ingredient in a therapeutically effective amount to protect against neuron damage.